2010
DOI: 10.1177/0312896209351451
|View full text |Cite
|
Sign up to set email alerts
|

The book-to-market equity ratio as a proxy for risk: evidence from Australian markets

Abstract: Crucial to the interpretation of the Fama and French three-factor model is the question of whether the book-to-market equity ratio should be assigned as a 'risk-based,' as opposed to a 'mispricing' explanation of share price formation. In the context of Australian stock markets, we examine the role of the book-to-market equity ratio in the formation of stock returns. Notwithstanding the distinctive characteristics of Australian markets, our findings are complementary with findings for U.S. stocks. We succeed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 32 publications
5
20
1
1
Order By: Relevance
“…The results of recent survey confirmed previous results that the B\M ratio is positively related to stock returns [27]. However, [28] found that the B/M ratio has a principal role in the formation of sock returns, and the relationship between stock returns and B/M ratio due to the attraction of B/M ratio to the implications of market leverage that include the risk factors, which play the effective roles in stock return predictability. Therefore, the B/M as a predictor has an explosive impact on stock returns.…”
Section: Book-to-market Ratio (B/m) and Stock Returnsupporting
confidence: 78%
“…The results of recent survey confirmed previous results that the B\M ratio is positively related to stock returns [27]. However, [28] found that the B/M ratio has a principal role in the formation of sock returns, and the relationship between stock returns and B/M ratio due to the attraction of B/M ratio to the implications of market leverage that include the risk factors, which play the effective roles in stock return predictability. Therefore, the B/M as a predictor has an explosive impact on stock returns.…”
Section: Book-to-market Ratio (B/m) and Stock Returnsupporting
confidence: 78%
“…3 The current paper complements and extends the analysis of Chiah et al (2016) in a number of ways. First, whereas Chiah et al (2016) are primarily concerned with comparing the "fit" of the five-factor model to three-factor and 1 See, for example, Halliwell et al (1999), Gaunt (2004), Faff (2004), Demir et al (2004), Dempsey (2010), Galariotis (2010), and Brailsford et al (2012b). 2 For example, the fit of an asset pricing model is examined in a multivariate context using the Gibbons et al (1989) F andHansen (1982) J tests, whilst the average R 2 across test assets is a more-crude measure of fit.…”
Section: Introductionmentioning
confidence: 99%
“…See, for example, Halliwell et al (), Gaunt (), Faff (), Demir et al (), Dempsey (), Galariotis (), and Brailsford et al ().…”
unclassified
“…In the above model, leverage (LEV) is used as a measure of risk and a control variable similar to Dempsey (2010).…”
Section: Methodsmentioning
confidence: 99%